UPAYA MENINGKATKAN MOTIVASI ANAK-ANAK PUTUS SEKOLAH MELALUI SEKOLAH PAKET DI DESA KUTA - Sana, Nur Nisfi; Yuwanda Aprilia, Restu; Fidia Putri, Naila; Mega Putri Oktavianti, Dinda; Nur Rizkiah, Siti; Azzahra, Noviandra; Prasetyo, Teguh (Universitas Djuanda, 2024)
This community service activity aims to motivate out-of-school children to return to school through school packages. This research included out-of-school children aged 13-16 years in Kuta Village, especially in Warudoyong Village Rt 02 Megamendung District. Data collection was carried out through observation and interviews. The data was analyzed descriptively and qualitatively with the stages of data collection, data reduction, and conclusion. The results of this program reveal that children who have dropped out of school in Kuta Village have various reasons for taking package schools, including economic constraints, the impact of the COVID-19 pandemic, environmental influences, and family support. The children decided to attend a package school organized by PKBM as an alternative to continuing their education. This package school is presented with an exciting and interactive learning approach, including digital technology and outdoor activities. There are three main factors revealed, namely: (1) economics, (2) environment, and (3) motivation play an essential role in the decision of out-of-school children to take package schools. Even though they face several challenges, such as feeling lazy in studying, these children feel motivated to continue their education to a higher level after completing package school. This program shows the importance of government, schools/universities, and families' collaborative efforts in supporting out-of-school children to get a better education and achieve their dreams.